ESTRATÉGIAS DE ENSINO DO EMPREENDEDORISMO: UMA CONTRIBUIÇÃO VOLTADA PARA A FORMAÇÃO DE ADMINISTRADORES DO CURSO DE GRADUAÇÃO - Azevedo, Solange Coelho de (2004)
The IES Instituições de Ensino Superior ( College Education Institutions ) have been gathering forces to form professionals with entrepreneurship competence due to the educational necessities and the transformation effects in this new era. Therefore, in order to answer the questions: What do you teach? and How do you teach? , this paper was elaborated to propose strategies, actions and a possible educational approach to help teachers develop professionally competent and able students in business administration, contributing to an education based on the objectives of the business administration graduation course. Criteria for evaluating learning efficiency will be proposed and indicated as a discipline in the curricular grid, to be more adequate in the learning specifications. Nevertheless, this paper presented here as a proposition is based on the researcher s vision as a professor of this entrepreneurship discipline, it needs to be applied in order to measure effectiveness this proposed.